What's the diagnosis? Organisational culture and palliative care delivery in residential aged care in New Zealand. (26th March 2015) - Frey, Rosemary; Boyd, Michal; Foster, Sue; Robinson, Jackie; Gott, Merryn
Abstract: Organisational culture has been shown to impact on resident outcomes in residential aged care (RAC). This is particularly important given the growing number of residents with high palliative care needs. The study described herein (conducted from January 2013 to March 2014) examined survey results from a convenience sample of 46 managers, alongside interviews with a purposively selected sample of 23 bereaved family members in order to explore the perceptions of organisational culture within New Zealand RAC facilities in one large urban District Health Board. Results of the Organisational Culture Assessment Instrument (OCAI) completed by managers indicated a preference for a 'Clan' and the structured 'Hierarchy' culture. Bereaved family interviews emphasised both positive and negative aspects of communication, leadership and teamwork, and relationship with residents. Study results from both managers' OCAI survey scores and next of kin interviews indicate that while the RAC facilities are culturally oriented towards providing quality care for residents, they may face barriers to adopting organisational processes supportive of this goal.